Network Analysis of Different Strategic Network in Indonesian Music Industry towards Value Creation. Case: Guvera Indonesia and Indonesia Netlabel Union - Suwondo, Merwyn; Dellyana, Dina (Journal of Business and Management, 2016)
Abstract. The music industry is continually changing to adapt to the changes in technology, distribution platform, and also in the development of the product. In this digital era, now artists can introduce their works to the consumer all around the world easier. Currently, music industry total revenues grew 3.2 percent to US 15.0 billion, leading to the industry's first significant year-on-year growth in nearly two decades. Streaming remains the fastest-growing source of income in the music industry. Revenues increased 45.2 percent to US 2.9 billion, which over the five-year period up to 2015, have grown more than four-fold.The digital era is the one of the most drastic changes in music industry, with digitalization now music can be spread and listened all over the world. For those who can see this as opportunity can work their business model and system to adapt with that era. But, there is company who see this as a thread, because the digitalization of music is ruining the business.To conduct the research, network structure, behavior, and governance are required as main data to be analyzed. To find the value creation, the researcher conducted semi-structured interview approach which also involves analysis to finds its value creation.The result of this research will give an explanation about Indonesian Netlabel Union and Guvera Indonesia networks characteristic and their value creation. Also, give recommendations for both of the network.Keywords: Value Creation, Strategic Network, Network Structure, Network Governance, Network Behavior, Qualitative Research, Indonesian Music Industry